Environmental sociology risk and sustainability in modernity - Lenzi, Cristiano Luis (Lexington Books, 2022)
"Environmental Sociology: Risk and Sustainability in Modernity examines the encounter between sociology and contemporary environmental issues. It presents the proposal for an environmental sociology considering the dilemmas surrounding sustainable development, ecological modernization, and risk society"--